Pendidikan Sufi Datuk Tiro dan Pengaruhnya Bulukumba - Muhammad Room (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2007)
Muhammad saw before become a prophet (a messenger of God) always contemplated at mountcave Hira,this is showed his mysticism. He continued this way of life and followed by his followers as calledAhl alSuffah. In Indonesia, there is term called Walisongo (nine holy men) who has spreaded Islam in Nusantara (Java).Several members of them who has spreaded Islam out of Java (in Sulawesi) are Abdul Jawad Khatib Bungsu Maulana Datuk Tiro (Datuk Tiro),Khatib Tunggal Abdul Makmur (Datuk Ribandang) dan Khatib Sulaiman (Datuk Pattimang).